Virtual Reality and Augmented Reality for Heart Failure Patients: Literature Review: Virtual Reality dan Augmented Reality Bagi Pasien Gagal Jantung: Literature Review - Kusumastuti, Kartikaningtyas; Herawati, Tuti (Essential English Grammar, 2024)
Virtual reality (VR) and augmented reality (AR) in the health sector are increasingly being used. However, there is limited study on the use of VR and AR in nursing care for heart failure. Long-term care for heart failure patients is a challenge as well as an opportunity for nurses to apply VR and AR, so that therapy modalities become more varied, interesting, and increase patient compliance. The aim of this literature study is to explore the use of VR and AR for heart failure patients. Articles were obtained from the ScienceDirect, PubMed, Clinical Key, SAGE, ProQuest and SpringerLink databases published in 2019-2023, using the keywords "virtual reality", "augmented reality", and "heart failure". The use of VR and AR in heart failure embraces the areas of patient care, both inpatient and outpatient. This study shows that VR and AR have a positive impact for heart failure patients. This technology can reduce patient’s level of pain and anxiety, and it also improve patient experience and participation in rehabilitation programs. Nurses can use this technology in almost all stages of the nursing process, from assessment to nursing implementation. Further studies are needed regarding VR and AR in cardiovascular nursing care that can be applied in Indonesia.